Bilateral middle cerebellar peduncle compromise due to hypoglycemic encephalopathy: A case report and literature review - Sara Henao Romero, MD; Daniel Villamizar Torres, MD; Diego M. Rivera, MD (Radiology Case Reports, 2022)
Hypoglycemic encephalopathy constitutes a critical presentation of severely diminished glucose levels. We present the case of a 53-year-old male patient with a history of diabetes mellitus with hypoglycemic encephalopathy and MRI findings of bilateral middle cerebellar peduncle lesions. Common findings of hypoglycemic encephalopathy described in the literature consist of bilateral compromise of the cerebral cortex, basal ganglia, hippocampus, and long tracts of white matter. The cerebellum and brainstem are usually not affected. This is the ninth report of cerebellar peduncle compromise with hypoglycemia. As increasing evidence regarding prognosis estimation of lesion distribution arises, we consider it important to report the different cases of rare patterns of compromise.